The role of nurses and midwives in the promotion of sexual health - Kouta, Christiana (My University, 2005)
Globally, within the health promotion thematology sexual health seems to problematize nursing researchers. There are several factors in nursing, such as stereotypes, that negatively affect the image and perception of the nurse. Sexual health is an important factor for the well-being and quality of one's life. This article reviews the role of the nurses according to their specialization or the department they work in.
Keywords: Nurses; Midwives; Sexual health; Health promotion; Nursing; Nursing researchers